A Study on Efficiency of DC Home System over AC Home System in Low Power Appliances - Osman, Muhammad Fizwadi (2017)
DC System technology is getting evolved worldwide, especially in the distribution system. The increase of development in renewable energy sources (RES), solar energy, especially makes DC Home System is reliable to be used in the future. There is a lot research conducted stated that DC Home System is much better than conventional AC Home System. However, this statement is still a question regarding its efficiency. This project is to study and develop a new DC off-grid home system as an alternative to the AC conventional home system. DC home system are beneficially in DC generation and storage, loads, efficiency and conversion stage reduction. The scope in this project would be based on low voltage home system which applied in rural area, villages, and small homes that having low power home appliances. A modelling of AC and DC Home System will be designed and implemented in a method of simulation using MATLAB Simulink. Besides, there will be a model prototype to be experimented and analyzed the system efficiency. The results show the efficiency of DC Home System is 15% higher than AC Home System. Besides, this project discovered the losses of AC and DC Home System are affected by utilization of conversion component such as inverter and rectifier. Further improvement and discussion can be made in the DC Home System so that it will be beneficially used in high power home appliances.